VALIDITAS MODUL PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATERI SEL KELAS XI SMA - H. Husain, Ilyas; D. Mamu, Hartono; Mardin, Herinda; Yasser Arafat, Muhammad; Maryati Yusuf, Frida (Jurnal Biogenerasi, 2024)
Augmented Reality (AR) is a technology that is one of the new innovations in learning by displaying images in 3D form which makes abstract concepts more real, such as students can observe cell models directly through Augmented Reality visualization. This research aims to test the validity of Augmented Reality-based learning modules in class XI SMA cell material. This type of development research or Research and Development (R&D) uses the ADDIE development model which is carried out up to the development stage, namely validity testing. The results of the validity test show that the Augmented Reality-based learning module on cell material obtained an average validity value of 94% by material experts and validation carried out by media experts showed an average of 75.38% which meets validity standards. Based on these results, this module was declared valid and suitable for use in learning.